Cellular and humoral immune responses in sheep vaccinated with candidate antigens MAP2698c and MAP3567 from Mycobacterium avium subspecies paratuberculosis - Gurung, Ratna B.; Purdie, Auriol C.; Whittington, Richard J.; Begg, Douglas J. (Frontiers in Cellular and Infection Microbiology, 2014)
Control of Johne’s disease, caused by Mycobacterium avium subspecies paratuberculosis (MAP) in ruminants using commercially available vaccine reduces production losses, mortality, faecal shedding and histopathological lesions but does not provide complete protection from infection and interferes with serological diagnosis of Johne’s disease and bovine tuberculosis. At this time no recombinant antigens have been found to provide superior protection compared to whole killed or live-attenuated MAP vaccines. Therefore, there is a need to evaluate more candidate MAP antigens. In this study recombinant MAP antigens MAP2698c and MAP3567 were formulated with four different MONTANIDE (ISA 50V2, 61VG, 71VG and 201VG) adjuvants and evaluated for their ability to produce specific immune responses in vaccinated sheep. The cellular immune response was measured with an interferon-gamma (IFN-γ) release assay and the humoral immune response was measured by antibody detection enzyme linked immunosorbent assay. Recombinant vaccine formulation with the antigen MAP2698c and MONTANIDE ISA 201VG adjuvant produced strong whole-MAP as well as MAP2698c-specific IFN-γ responses in a high proportion of the vaccinated sheep. The formulation caused less severe injection site lesions in comparison to other formulations. The findings from this study suggest that the MAP2698c + 201VG should be evaluated in a challenge trial to determine the efficacy of this vaccine candidate.